Workers, unions and politics : Indonesia in the 1920s and 1930s - Ingleson, John. (Leiden : Brill, 2014)
"In Workers, Unions and Politics : Indonesia in the 1920s and 1930s, John Ingleson revises received understandings of the decade and a half between the failed communist uprisings of 1926/1927 and the Japanese occupation in 1942. They were important years for the labour movement. It had to recover from the crackdown by the colonial state and then cope with the impact of the 1930s depression. Labour unions were voices for greater social justice, for stronger legal protection and for improved opportunities for workers. They created a discourse of social rights and wage justice. They were major contributors to the growth of a stronger civil society. The experiences and remembered histories of these years helped shape the agendas of post-independence labour unions"--
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Labor movement -- Indonesia -- History -- 20th century; Labor unions -- Indonesia -- History -- 20th century; Industrial relations -- Indonesia -- History -- 20th century; Indonesia -- History -- 20th century; Electronic books